Using discrete event simulation to optimise cementing resources: a case study analysis using a call-out strategy for onshore rigs. (5th October 2022) - Dsouza, Maclean Iral; Watfa, Mohamed K.
A standard resource configuration is to allocate one cementing package for each rig, which does not utilise the capital-intensive cement unit resource optimally. The objectives of this study are to study the economic implications of the proposed call-out strategy, an implementation of the just-in-time philosophy and develop a discrete event simulation (DES) model improve operations' efficiency. To demonstrate the practicality of our model, three case studies with real collected data over a period of five years for a leading oil and gas company in the Gulf area were considered and the relationship between the optimal number of cementing units and the number of rigs was rigorously analysed: optimal number of cement units = 1.489 + 0.525 (number of rigs). Results indicate that optimisation of the cementing units and human resources can be achieved with effective resource reallocation to different rig configurations while considering realistic factors of capacity planning, efficiency utilisation and delivery of cementing services without non-productive time.